Implementation of sprinkling location with restructure-monochrome-dot on diffusivity mutational-status of fabricated function agent on porous - Kim, Jeong Lae; Park, Beom Seok (Edelweiss Applied Science and Technology, 2024)
The recognition technology that determines the sprinkling mutation status in simple squamous epithelium cells produces a monochromatic dot pattern in an echo state using the instantaneous recognition rate (MPR) and vacuum recognition rate (VPR). The diffusivity echo system was created in the form of sprinkler recognition to control recognition rate conditions. The mutation status of simple squamous epithelium cells is displayed as a sprinkling porous value according to the sprinkling location layer by a diffusivity-down structure to search as a jagged monochrome-dot pattern. In the sprinkling porous, the perception rate concept is verified by referencing the instantaneous rate and vacuum rate to the mutant state signal through the sprinkling echo conformation. The jagged mutation state of MPR-VPR appears from a sprinkling porous to a maximum-minimum sprinkling-echo conformation. Sprinkling echo locations are found in the sprinkling porous values of the mutant state. Wr-af-FA-τMED is far mutational-status of 18.12±5.16 units, Wr-af-CO-τMED is convenient mutational-status of 6.89±0.30 units, Wr-af-FL-τMED is flank mutational-status of 2.34±1.53 units, Wr-af-VI-τMED is vicinage mutational-status of 0.48±0.20 units. Diffusivity echo calculates the jagged momentary vacuum conformation that appears through the perception rate system in simple squamous epithelium cells, and the ability to estimate the sprinkling-echo conformation for the jagged degree perception rate of MPR-VPR can be confirmed. We can estimate the shape through the vacuum signal in the sprinkling porous and estimate the diffusion data of the diffusivity echo rate through the diffusivity perception system.